Constipation and its Management according to Ayurveda: Ayurvedic Approaches to Managing Constipation (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Clearing of bowels is a step towards good health. There is a feeling of being uncomfortableand routine work is hampered when the bowels of a person are not cleared. Constipation is one of themost common gastrointestinal complaints all over the world resulting in over two million reported casesannually. The prevalence of constipation around the globe is about 10 whereas in India it is about 14higher than the world average.Generally, a person is considered to be constipated when bowel movements result in the passage ofsmall amounts of hard and dry stool, usually fewer than three times a week. WHO reports that more than80 of the world's population specially in developing in develops countries dependent on herbalmedicine.Constipation can be broadly classified into two types a) Casual or temporary b) Chronic or habitual.Ayurveda describes in Charaka samhita and Sharangdhara Samhita various herbs and their preparationsfor restoring normal evacuation of GI tract. These include – Vatanulomaka (Carminative), Sramsana(Laxative), Bhedana (Purgative) and Rechana (Cathartics). The present communication deals with themanagement of constipation with its Ayurvedic perspectives and mode of action of Ayurvedic andmodern aspects.